One piece. Collection no. 10 [videorecording (DVD)]. (FUNimation, 2014)
Hoping to save their beloved boat, the Straw Hats drop anchor at the shipbuilding city of Water 7, but the prognosis for the Going Merry proves far worse than expected. The hits keep coming as Robin mysteriously vanishes, the Franky Family robs the crew blind, and Usopp goes rogue after a shocking battle with Luffy! As if things weren't bleak enough, the gang finds themselves accused of a cold-hearted assassination attempt, and hunted by the entire city.